The International Penal Court and the incidencen in the Colombian armed conflict - Tolosa Suárez, Juan Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2012)
The article makes a brief account of the birth of the International Humanitarian Rights, the creation of International Criminal Courts and, in particular, t the creation of  the International Criminal Court (ICC) and its competence to analyze its incidence  in the ratification and submission to the Statute of the International Criminal Court in the internal armed conflict by Colombia, in order to discover whether effectively  has been an important subjugation of the country to contribute to the International Criminal Court to achieve the peace process, temperance or decrease of the Colombian conflict.